Isolasi Lignin Dari Jerami Padi Dengan Metoda Klason - Hotni Lamtiar; Elvi Yenie; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Lignine is a complex polimer with high molecular weight which compiled of fenilpropane units. This study aims to know concentration of NaOH influence and delignification time of rice straw influence againts sucrose content of rice straw. Analysis of lignine purity using Klason Method. Isolation of waste rice straw are extraction, hydrolysis, delignification, and purity by using Klason Method. Extraction process be done on variety ofNaOH catalyst concentration (4%, 6%, 8%) in hydrolisis process and delignification time (1 hour, 11/2 hour, and 2 hour) . The best hydrolisis result is 8%, the best delinification time is 1 jam with concentration 8% NaOH in the process of ripening and the highest purity of lignine is 3,14%. The result of delignification will be analized its lignine concentration usingfor Fourier Transform Infra Red (FTIR) to know its function cluster.Keywords: Delignification, Extraction, FTIR, Hydrolisis, Rice Straw, Lignine, Klason Method